GAMBARAN UMUM SISA MAKANAN DAN STATUS GIZI PADA PASIEN HIPERTENSI YANG MENERIMA DIET RENDAH GARAM DI RUMAH SAKIT SULTAN SYARIF MOHAMAD ALKADRIE PONTIANAK - Welviana, Isabelita; Waliyo, Edy (Pontianak Nutrition Journal, 2018)
Low-salt diets affect the patient’s appetite because restricted salt will affect the taste of food. A decrease in appetite due to the taste of food causes the patient not to consume the portion of food served which results in his nutritional needs not being met. This study aims to determine the general description of food residue and nutritional status in hypertensive patients who receive a low-salt diet at Sultan Syarif Mohamad Alkadrie Pontianak Hospital, the type of research used was descriptive with cross sectional design, the number of samples studied were 41 people. The data used consisted of two types, namely primary data including nutritional status data based on BMI, identity data and food waste data. While secondary data covers the general state of the sample research location. The results showed that respondents who had a good food intake of 43.9% and those who had less food intake were 56.1%. The most common type of leftovers found in respondents were animal dishes at 41%. It was found that respondents with overweight nutritional status were 14.6% (6 people) and underweight nutritional status of 19.6 (8 people). It is advisable to further improve the type and taste of food, so that patients do not get bored quickly and are able to spend the food given by the hospital, so that nutritional status the patient is awake during hospitalization.